Phosphodiesterase Methods and Protocols - Lugnier, Claire; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2005)
The multigenic family of cyclic nucleotide phosphodiesterases (PDEs) is now known to offer many new therapeutic possibilities through their influence over intracellular signaling, though their precise cell mechanisms to modulating that process remain uncertain. In Phosphodiesterase Methods and Protocols, a panel of research leaders in the PDE field describes new concepts and techniques for investigating the role of PDEs in orchestrating normal and pathophysiological responses. Presented in step-by-step detail, these readily reproducible methods allow the measurement of cyclic nucleotide variations in living cells, as well as their visualization in a spatiotemporal manner, the localization and characterization of their activities in tissues and living cells, and the assessment of targeted PDEs in creating specific tools and drugs. Additional chapters discuss the generation of PDE4 knockout mice to demonstrate not only the potential role of targeted PDEs, but also their use in further studies of the central role of PDE regulation in intracellular signaling control. These techniques offer clinicians a way to find new therapies for numerous pathologies whose molecular origins are unknown and whose treatment is symptomatic. Alterations of intracellular signaling related to PDE deregulation in such pathologies as inflammation, neurodegeneration, and cancer may explain the difficulties observed in their prevention and treatment. The protocols follow the successful Methods in Molecular Biology™ series format, each offering step-by-step laboratory instructions, an introduction outlining the principle behind the technique, lists of the necessary equipment and reagents, and tips on troubleshooting and avoiding known pitfalls. Path-breaking and highly practical, Phosphodiesterase Methods and Protocols offers cell biologists, molecular biologists, pharmacologists, and medicinal chemists a broad ranging survey of the advanced tools and concepts needed to understand the role of PDEs in physiological functions, their implications in several critical pathologies, and the opportunities they offer for new drug design.
Study of Cyclic Adenosine Monophosphate Microdomains in Cells -- High-Resolution Measurements of Cyclic Adenosine Monophosphate Signals in 3D Microdomains -- Cygnets -- High-Throughput Screening of Phosphodiesterase Activity in Living Cells -- Assessment of Phosphodiesterase Isozyme Contribution in Cell and Tissue Extracts -- Localization of the Cyclic Guanosine 3?,5?-Monophosphate- Hydrolyzing Phosphodiesterase Type 9 in Rat Brain by Nonradioactive In Situ Hybridization -- Determination of Ca2+/Calmodulin-Stimulated Phosphodiesterase Activity in Intact Cells -- Adenovirus-Mediated Overexpression of Murine Cyclic Nucleotide Phosphodiesterase 3B -- Identification of Promoter Elements in the 5?-Flanking Region of Murine Cyclic Nucleotide Phosphodiesterase 3B Gene -- Purification of PDE6 Isozymes From Mammalian Retina -- Cyclic Guanosine 5?-Monophosphate Binding to Regulatory GAF Domains of Photoreceptor Phosphodiesterase -- Renaturation of the Catalytic Domain of PDE4A Expressed in Escherichia coli as Inclusion Bodies -- Determining the Subunit Structure of Phosphodiesterases Using Gel Filtration and Sucrose Density Gradient Centrifugation -- Crystallization of Cyclic Nucleotide Phosphodiesterases -- Generation of PDE4 Knockout Mice by Gene Targeting -- Immunoprecipitation of PDE2 Phosphorylated and Inactivated by an Associated Protein Kinase -- Investigation of Extracellular Signal-Regulated Kinase 2 Mitogen-Activated Protein Kinase Phosphorylation and Regulation of Activity of PDE4 Cyclic Adenosine Monophosphate-Specific Phosphodiesterases -- Radiolabeled Ligand Binding to the Catalytic or Allosteric Sites of PDE5 and PDE11 -- Analysis of Dimerization Determinants of PDE6 Catalytic Subunits -- Interactions Between Catalytic and Inhibitory Subunits of PDE6 -- Purification, Reconstitution on Lipid Vesicles, and Assays of PDE6 and Its Activator G Protein, Transducin.
Keywords: Biochemistry; Biochemistry, general